2019
DOI: 10.1108/jhtt-03-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Presenting hotels in virtual reality: does it influence the booking intention?

Abstract: Purpose The purpose of this study is to investigate the effects of telepresence while using a smartphone-based virtual reality system (SBVR) to explore a hotel virtually and to determine the influence of this immersive experience on the booking intention of the potential customer. Design/methodology/approach Within the scope of this study, a conceptual research model was developed which covered utilitarian and hedonic aspects of the user experience of SBVRs and showed their relevance for the booking intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 51 publications
3
42
0
Order By: Relevance
“…ere are many unknown factors that can get the expected effect after the design is put on the market. If we can predict the degree of market response in the future and solve the problems and deficiencies in the design in time [18], then these unknown factors will inevitably be transformed, allowing designers and producers to make correct market decisions and reducing risk factors to improve the efficiency and success rate of the design [19,20].…”
Section: Extraction Of Elements From Lingnan Cultural Productsmentioning
confidence: 99%
“…ere are many unknown factors that can get the expected effect after the design is put on the market. If we can predict the degree of market response in the future and solve the problems and deficiencies in the design in time [18], then these unknown factors will inevitably be transformed, allowing designers and producers to make correct market decisions and reducing risk factors to improve the efficiency and success rate of the design [19,20].…”
Section: Extraction Of Elements From Lingnan Cultural Productsmentioning
confidence: 99%
“…The more useful the information and the more it feels in accordance with what is needed by potential boutique hotel visitors, the intention to book a boutique hotel will also increase and in line with [9]. Similar research in different contexts also found similar results, hotel virtual presentations tends to be a useful for evaluating hotels, it will increase the intention to book hotels and give an indication that the utilitarian value of using hotel virtual presentations is an important factor [10].…”
Section: Discussionmentioning
confidence: 53%
“…If travelers find a review of a hotel that is considered helpful, they will see the utilitarian value of the review, conversely if they find that the review is a pleasant review, what they see is the hedonic value of the review [8]. Utilitarian value represented by perceived usefulness and hedonic value represented by perceived enjoyment [10]. Perceived usefulness and perceived enjoyment as derived attributes of a review can be something useful and fun to read and have an influence on online purchase intentions [9].…”
Section: Perceived Value Of Online Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Israel, Zerres & Tscheulin (2019) state that travelers' usefulness of virtual information (reviews, videos etc.) influence their online hotel booking intentions.…”
Section: Introductionmentioning
confidence: 99%